ANTI-NICOTINE VACCINES: NEW PERSPECTIVE FOR SMOKERS AND CHRONIC OBSTRUCTIVE PULMONARY DISEASE (COPD) - Marsheilla Riska (Fakultas Kedokteran Universitas Lambung Mangkurat, 2017)
Abstract: Smoking and Chronic Obstructive Pulmonary Disease (COPD) become a global problem in the world. The increasing number of smokers in the world also led to significantly increased morbidity and mortality due to COPD. Many attempts were made, ranging from government policy that prohibits smoking in public places, to pharmacological therapy, and psychotherapy for smokers. However, often there is a failure to quit smoking. Dependence on nicotine is an important factor that causes someone failed to stop smoking. As for the pharmacological therapy is currently widely used to intervene in nicotine dependence, such as nicotine replacement therapy, bupropion, and varenicline. However, existing therapies have not given satisfactory results in reducing smoking rates and the number of COPD significantly. Therefore, the anti-nicotine vaccine that is currently in development and research, such as NicVAX, NIC002, TA-NIC, and SEL-068, become a new perspective for smokers to stop smoking and prevent long term recurrence. Keywords: nicotine, anti-nicotine, smoking, COPD